2019
DOI: 10.1007/s12630-019-01370-3
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative pain management and chronic postsurgical pain after elective foot and ankle surgery: a scoping review

Abstract: Purpose Chronic postsurgical pain (CPSP) can occur after elective mid/hindfoot and ankle surgery. Effective treatment approaches to prevent the development of CPSP in this population have not been extensively investigated. The impact of multimodal strategies to prevent CPSP following elective mid/hindfoot surgery is unknown because of both the heterogeneity of acute pain management and the lack of a recognized definition particular to this surgery. This review aimed to identify

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Foot surgery often causes serious and prolonged postoperative pain [ 19 ]. The primary aim of this study was to explore an effective method of analgesia for patients with unilateral calcaneal fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Foot surgery often causes serious and prolonged postoperative pain [ 19 ]. The primary aim of this study was to explore an effective method of analgesia for patients with unilateral calcaneal fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain after major elective ankle and hindfoot surgery (ankle arthrodesis, subtalar arthrodesis, triple arthrodesis) is often severe for several days—especially the first two postoperative days 1,3,4,6. Daily mean in‐hospital opioid consumption has been reported at ranges of approximately 10–30 mg oral morphine‐equivalent doses15 (with much higher doses in intermittent or long‐term preoperative opioid users), despite multimodal analgesic regimes including single‐dose PNB or cPNB 6,9,16. Either single‐dose PNB or cPNB is conventionally recommended as a component of multimodal analgesia in order to alleviate postoperative pain after major ankle and hindfoot surgery 4.…”
Section: Discussionmentioning
confidence: 99%
“…Focus on optimal postoperative pain management may also be paramount for the reduction of chronic postsurgical pain since clinical studies have shown a strong association between acute and chronic postsurgical pain 4,16,31. The incidence of chronic postsurgical pain is 10%–50% and may be much higher in specific populations of patients—for example, post‐amputation 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work was part of a multi-phase evaluation of current evidence and current practice patterns for pain management after elective foot and ankle surgery. Our initial scoping review found sparse evidence for pain management, with few randomized trials, all of which investigated short-term pain outcomes following a perioperative nerve block [ 28 ]. In addition, after this evaluation of local prescribing practices, we undertook an international Delphi Consensus process to develop consensus-based guidelines for pre-, peri- and post-operative pain management following elective foot and ankle surgery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%